NEURAL NETWORK FOR RECOGNIZING SIGNAL-SHAPE•OF NUCLEAR DETECTOR OUTPUT - Mardiyanto M Panitra (BATAN, 2006)
ABSTRACTNEURAL NETWORK FOR RECOGNIZING SIGNAL- SHAPE OF NUCLEAR DETECTOR OUTPUT. The use of artificial intelligent technique in the engineering field has been familiar especially in the field of pattern recognition. By using this technique either simple routine works or complicated routine works can be done by the help of a d1g1tal camera and a personal computer.. One of the complicated works that can not be solved easily is how to separate two kinds of nuclear radiation types wnich are mixed in the same field. The separation of the two kinds of radiation become is very important for the radiation dosimetry purposes.. For doing this we have carried out a preliminary research in applying a neural network technique for recognizing C and T letters with right, left, up, and down positions. We arranged a three-layer neural network i.e. input layer (9 neurons with/without 1 bias neuron), hidden layer (11 neurons), and output layer (1 neuron). From this preliminary study the use of a bias neuron gave faster learning process compared with the one without the bias neuron. The neural network could work successfully in determining the letter S and T without any mistake. ABSTRAKPENGGUNAAN NEURAL NETWORK UNTUK MEMBEDAKAN BENTUK SINYAL KELUARAN DARI SEBUAH DETEKTOR NUKLIR. Pemakaian teknik jaringan di dalam bidang keteknikan sudah sangat dikenal terutama untuk membedakan bentuk suatu sinyal. Dengan menggunakan teknik ini baik pekerjaan rutin yang sederhana maupun pekerjaan rutin yang sulit dapat dilakukan secara otomatis dengan bantuan sebuah komputer pribadi dan sebuah kamera digital. Dalam bidang dosimetri nuklir, pemisahan antara dua jenis radiasi merupakan hal yang sangat penting. Untuk tujuan itu kami melakukan penelitian untuk menggunakan system jaringan tiruan neural network untuk membedakan dua buah huruf yakni huruf C dan T dengan 4 posisi yang berbeda. Untuk tujuan itu digunakan jaringan tiruan dengan 9 input neuron, 11 neuron pada lapisan tengah dan 1 neuron pada keluarannya. Dari penelitian ini diperoleh hasil bahwa dengan menggunakan 1 bias neuron pada lapisan input dapat mempercepat proses pembelajaran yakni dari 10 iterasi menjadi 5 iterasi. Setelah dilakukan pembelajaran maka jaringan mempu membedakan kedua huruf dalam 8 posisi tanpa adanya kesalahan.